2012
DOI: 10.1128/mcb.01067-12
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphatidylinositol 3-Kinase–Pax3 Axis Regulates Brn-2 Expression in Melanoma

Abstract: bDeregulation of transcription arising from mutations in key signaling pathways is a hallmark of cancer. In melanoma, the most aggressive and lethal form of skin cancer, the Brn-2 transcription factor (POU3F2) regulates proliferation and invasiveness and lies downstream from mitogen-activated protein kinase (MAPK) and Wnt/␤-catenin, two melanoma-associated signaling pathways. In vivo Brn-2 represses expression of the microphthalmia-associated transcription factor, MITF, to drive cells to a more stem cell-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 58 publications
(86 reference statements)
0
50
0
Order By: Relevance
“…14,16 Meanwhile, PAX3 seems to repress MITF expression through POU3F2 (see below) in some melanomas. 17,18 α-Melanocyte-stimulating hormone (α-MSH) increases pigmentation through increasing tyrosinase (Tyr) expression in mouse B16-F1 melanoma cells, 19 as well as numerous additional pigmentation related genes (see below). Based on the results that α-MSH activates the cAMP-CREB signaling pathway and MITF activates TYR transcription, Bertolotto et al 20 and Price et al 21 hypothesized and found that cAMP-CREB signaling activates MITF-M transcription in a cis-acting fashion.…”
Section: Discovery Of Mitfmentioning
confidence: 99%
“…14,16 Meanwhile, PAX3 seems to repress MITF expression through POU3F2 (see below) in some melanomas. 17,18 α-Melanocyte-stimulating hormone (α-MSH) increases pigmentation through increasing tyrosinase (Tyr) expression in mouse B16-F1 melanoma cells, 19 as well as numerous additional pigmentation related genes (see below). Based on the results that α-MSH activates the cAMP-CREB signaling pathway and MITF activates TYR transcription, Bertolotto et al 20 and Price et al 21 hypothesized and found that cAMP-CREB signaling activates MITF-M transcription in a cis-acting fashion.…”
Section: Discovery Of Mitfmentioning
confidence: 99%
“…PAX3 drives melanoma migration and invasiveness, and this is due at least in part by the activation of the BRN2 gene (18).…”
Section: Discussionmentioning
confidence: 99%
“…PAX3 inhibition leads to a decrease in melanoma cell proliferation and survival (14 -17). PAX3 has also been implicated in melanoma migration, invasion, and metastasis (18). The mechanism by which PAX3 acts as an oncogene is poorly understood, although it most likely parallels its role during development by regulating growth and differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, silencing Pax3 using RNA interference was shown to inhibit proliferation, and induce terminal differentiation and apoptosis following activation of caspase-3 and p53 in melanoma cells [4][5][6]. More recently, Pax3 silencing was reported to inhibit the invasiveness of melanoma cells in culture [7] as well as the growth of melanoma cells with acquired resistance to vemurafenib [8]. PAX3 is also expressed in muscle progenitor cells before myogenic transcription factors, such as MyoD, Myogenin, and Myf5, and gradually decreases during muscle differentiation.…”
Section: Introductionmentioning
confidence: 99%